Long Term Effects of Ketogenic Low Carbohydrate and Low Fat Diets On Weight Loss, Risk of Dyslipidemia Risk, and Cardiometabolic Outcomes - Nana Wildana; Marhamah Marhamah; Nurul Rahmi; Rasmawati Rasmawati (SEHATI: Jurnal Kesehatan, 2026)
Weight loss and improvement in cardiometabolic risk are the primary goals of dietary interventions in populations at risk for obesity and dyslipidemia. Low-carbohydrate ketogenic diets (including VLCDs) and low-fat diets are two popular approaches, but their long-term effects are controversial. This systematic review aims to compare the long-term effects of low- carbohydrate ketogenic diets and low-fat diets on weight loss, dyslipidemia risk, and cardiometabolic outcomes in an adult population. A literature search of the PubMed, WOS, scilit Total records identified 4.179. After screening, 15 studies with a duration of at least 12 months were analyzed qualitatively and quantitatively. The ketogenic diet resulted in greater weight loss in the first 6–12 months, but 58% of subjects experienced an increase in LDL-C, despite improvements in triglycerides and HDL-C. The low-fat diet more consistently reduced LDL-C and triglycerides and increased HDL-C, although weight loss was slower. In the period 24 months, the difference in weight loss narrowed, but the risk of dyslipidemia in the ketogenic diet still needs to be watched out for. In conclusion, the ketogenic diet is effective for short-term weight loss and improvements in several lipid parameters, but can increase the risk of LDL-C. A low-fat diet is safer for long-term lipid profiles. Diet selection should be adjusted to the individual's risk profile and regular cardiometabolic monitoring.